Word order in Tibeto-Burman languages - Dryer, Matthew S. (2024)
This paper gives a detailed description of the word order patterns found among Tibeto-Burman languages. While Tibeto-Burmanists sometimes think that many Tibeto-Burman languages have some unexpected features for verb-final languages, this is by and large not the case. For example, verb-final languages in which one or more noun modifiers (adjective, demonstrative, numeral) follow the noun are very common elsewhere in the world. It is true that the majority of other verb-final languages in Asia put all modifiers before the noun, but it is in fact those other languages which are rather atypical crosslinguistically. The paper has separate sections on the two groups of languages in Tibeto-Burman which are VO, namely Karen and Bai. The rest of the paper focuses on the OV Tibeto-Burman languages, looking at six word order features that are not predictable from a language being OV, namely (1) adjective and noun; (2) relative clause and noun; (3) demonstrative and noun; (4) numeral and noun; (5) degree word and adjective; and (6) negative and verb. The patterns of the distribution of the various types is discussed in detail, both from a genealogical perspective and from a geographical one.